Segodnia v mire . Segodnia v mire . The World Today . Сегодня в мире - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Train accident in the Urals; elections in Poland; survey of Americans' attitudes towards Congress; curfew in Palestine; floods and the construction of protection barriers in Bangladesh; Environment Day in the United Kingdom. Contributors: Biriukov, Dmitrii (Anchor); Glavnaia redaktsiia mezhdunarodnoi zhizni (Studio) Series description: An information program of the Central Television of the USSR (CT USSR). The hosts were Igor Fesunenko, Valentin Zorin, Farid Seiful-Muliukov, and others. The program was first broadcasted on December 1, 1978 and was broadcasted until 1988. Железнодорожная катастрофа на Урале; выборы в Польше; опрос американцев об их отношении к Конгрессу; комендантский час в Палестине; наводнение и сооружение баррикад в Бангладеше; день защиты окружающей среды в Великобритании. Создатели: Бирюков, Дмитрий (Ведущий/Ведущая); Главная редакция международной жизни (Студия) Описание серии: Информационная телепередача Центрального телевидения СССР. Ведущие — Игорь Фесуненко, Валентин Зорин, Фарид Сейфуль-Мулюков и другие. Первый выпуск передачи вышел в эфир 1 декабря 1978 года. Выходила до 1988 года